Developing generic tools for characterizing agricultural systems for climate and global change studies (IMPACTlite - phase 2). Report to CCAFS - Rufino, Mariana C.; Quirós, Carlos F.; Boureima, Moussa; Desta, S.; Douxchamps, Sabine; Herrero, Mario; Kiplimo, Joyce; Lamissa D; Mango, Joash; Moussa, Abdoulaye S.; Naab, Jesse B.; Badiane Ndour, Ndèye Yacine; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Standard methods are needed to collect data to evaluate the performance of agricultural systems. Standardization allows comparisons across systems, and potentially the extrapolation of recommendations to similar development domains. The Integrated Modelling Platform for Mixed Animal Crop Systems (IMPACT, Herrero et al., 2007) is a data collection protocol and computer software tool designed to gather minimum datasets in smallholder crop-livestock systems. The protocol collects information ranging from household composition to crop and livestock production to household food consumption and household assets. Although IMPACTS s datasets are detailed to conduct a wide range of crop-livestock systems analysis, the data collection on the field proved to be time and resources demanding. The protocol works in monthly time steps i.e., most of the data is collected per month, thus it takes considerable time to complete an interview. The printed forms comprise over 30 different templates that resemble the screens in the software, and although this could speed up data entry, its use on the field for data collection often tends to be inoperative.